On Good ET0L Forms - Skyum, Sven (DAIMI Report Series, 1977)
This paper continues the study of ETOL forms and good EOL forms done by Maurer, Salomaa and Wood. It is proven that binary vomplete (short for very complete) ETOL forms exist and that no propagating or synchronized ETOL form can be vomplete.